Mass flourishing how grassroots innovation created jobs, challenge, and change - Phelps, Edmund S. (Princeton Princeton University Press, 2013)
Phelps explores what makes nations prosper--and why the sources of that prosperity are under threat today. Why did prosperity explode in some nations between the 1820s and 1960s, creating not just unprecedented material wealth but "flourishing"--meaningful work, self-expression, and personal growth for more people than ever before?
Includes bibliographical references (pages 337-349) and index.
Keywords: Economic history